Remote cadaveric minimally invasive surgical training - Miyano, Go; Takahashi, Makoto; Suzuki, Takamasa; Iida, Hisae; Abe, Eri; Kato, Haruki; Yoshida, Shiho; Lane, Geoffrey J.; Ichimura, Koichiro; Sakamoto, Kazuhiro; Yamataka, Atsuyuki; Okazaki, Tadaharu (Frontiers in Pediatrics, 2023)
Objective The aim of the study is to discuss the efficacy of live vs. remote cadaver surgical training (CST) for minimally invasive surgery (MIS). Methods A cohort of 30 interns in their first and second years of training were divided into three groups: live observers (n = 12), live participants (n = 6), and remote observers: (n = 12). The interns had the opportunity to either observe or actively participate in two different surgical procedures, namely, laparoscopic lower anterior resection, performed by a colorectal surgical team, and laparoscopic fundoplication, performed by a pediatric surgical team. The procedures were conducted either at a base center or at a remote center affiliated with the institute. Some of the interns interacted directly with the surgical teams at the base center, and others interacted indirectly with the surgical teams from the remote center. All interns were administered questionnaires before and after completion of the CST in order to assess their understanding of various aspects related to the operating room layout/instruments (called “design”), accessing the surgical field (called “field”), understanding of anatomic relations (called “anatomy”), their skill of dissection (called “dissection”), ability to resolve procedural/technical problems (called “troubleshooting”), and their skill in planning surgery (called “planning”) according to their confidence to operate using the following scale: 1 = not confident to operate independently; 4 = confident to operate with a more senior trainee; 7 = confident to operate with a peer; and 10 = confident to operate with a less experienced trainee. A p < 0.05 was considered statistically significant. Results All scores improved after CST at both the base and remote centers. The following significant increases were observed: for remote observers: “field” (2.67→4.92; p < .01), “anatomy” (3.58→5.75; p < .01), “dissection” (3.08→4.33; p = .01), and “planning” (3.08→4.33; p < .01); for live observers: “design” (3.75→6.17; p < .01), “field” (2.83→5.17; p < .01), “anatomy” (3.67→5.58; p < .01), “dissection” (3.17→4.58; p < .01), “troubleshooting” (2.33→3.67; p < .01), and “planning” (2.92→4.25; p < .01); and for live participants: “design” (3.83→6.33; p = .02), “field” (2.83→6.83; p < .01), “anatomy” (3.67→5.67; p < .01), “dissection” (2.83→6.17; p < .01), “troubleshooting” (2.17→4.17; p < .01), and “planning” (2.83→4.67; p < .01). Understanding of “design” improved significantly after CST in live observers compared with remote observers (p < .01). Understanding of “field and “dissection” improved significantly after CST in live participants compared with live observers (p = .01, p = .03, respectively). Out of the 12 remote observers, 10 participants (83.3%) reported that interacting with surgical teams was easy because they were not on-site. Conclusions Although all the responses were subjective and the respondents were aware that observation was inferior to hands-on experience, the results from both centers were equivalent, suggesting that remote learning could potentially be viable when resources are limited.